2012
DOI: 10.1128/aac.00276-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Linezolid on the 50% Lethal Dose and 50% Protective Dose in Treatment of Infections by Gram-Negative Pathogens in Naive and Immunosuppressed Mice and on the Efficacy of Ciprofloxacin in an Acute Murine Model of Septicemia

Abstract: cMurine models of infection were used to study the effect of linezolid on the virulence of Gram-negative bacteria and to assess potential pharmacodynamic interactions with ciprofloxacin in the treatment of these infections, prompted by observations from a recent clinical trial. Naive and immunosuppressed mice were challenged with Klebsiella pneumoniae 53A1109, K. pneumoniae GC6658, and Pseudomonas aeruginosa UC12120 in acute sepsis and pulmonary infection models, using different serial dilutions of these patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The higher ratios are suggestive of non-specific binding to the hydrophobic brain tissue, with repeated dosing. The lowest values were reached after week 4 (23.58 ± 6.1 lg/ml), these values were still significantly higher than the MIC's for a number of bacterial agents which cause central nervous system infections (Ager and Gould 2012;Marra et al 2012). This is demonstrated by studies which have showed the drug's efficacy against a large number of resistant CNS infections.…”
Section: Pharmacokinetic Analysis and Msi Analysismentioning
confidence: 83%
See 1 more Smart Citation
“…The higher ratios are suggestive of non-specific binding to the hydrophobic brain tissue, with repeated dosing. The lowest values were reached after week 4 (23.58 ± 6.1 lg/ml), these values were still significantly higher than the MIC's for a number of bacterial agents which cause central nervous system infections (Ager and Gould 2012;Marra et al 2012). This is demonstrated by studies which have showed the drug's efficacy against a large number of resistant CNS infections.…”
Section: Pharmacokinetic Analysis and Msi Analysismentioning
confidence: 83%
“…For the short term study, the animals received a single dose of LIN (100 mg/kg) which was prepared in 10 % DMSO, this was based on a previous study in which this amount was well tolerated in rodents and showed excellent kill characteristics in a murine model of septicaemia (Marra et al 2012). In the short term study, female Sprague-Dawley rats (with ad libitum access to food and water throughout the study) were given a single dose of LIN via oral gavage thereafter they were periodically sacrificed (0, 0.25, 0.5, 1, 2, 4, 6, 8 and 24 h; n = 3 per time-point) post-dose to determine the short term plasma and brain pK profile of LIN.…”
Section: Animal Studymentioning
confidence: 99%
“…Larvae were considered dead if they repeatedly did not respond to touch. The median lethal dose (LD 50 ) was calculated by nonlinear regression analysis using GraphPad Prism 5 (GraphPad, La Jolla) as (Marra et al ., 2012; Tietgen et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The method of LZD administration was based on a previous report. 12 Mice were administered 1 mL of LZD suspension (100 mg kg −1 , subcutaneous injection), 0.2 mL of NM suspension (30 mg kg −1 , intraperitoneal injection), or 0.2 mL of saline. Intraperitoneal injection of NM or saline was performed at 1 hour, 2 hours, 3 hours, and 4 hours after administration of LZD.…”
Section: Drug Administration and Blood Withdrawalmentioning
confidence: 99%